Beyond the HPA Axis: Progesterone-Derived Neuroactive Steroids in Human Stress and Emotion - Wirth, Michelle (Frontiers in Endocrinology, 2011)
Stress and social isolation are well-known risk factors for psychopathology. However, more research is needed as to the physiological mechanisms by which social support buffers the impacts of stress. Research in animal models suggests important roles for progesterone (P) and its product, the neuroactive steroid allopregnanolone (ALLO), in stress and psychopathology. These hormones are produced in brain and periphery during stress in rodents, and down-regulate anxiety behavior and HPA axis activity. Human clinical populations, including depressed patients, have alterations in ALLO levels, but it is unclear whether these basal hormone level differences have clinical import. To begin to address this question, this review examines the role of P and ALLO in stress physiology, and the impact of these hormones on mood, in healthy humans. Evidence largely supports that P and ALLO increase during stress in humans. However, P/ALLO administration appears to cause only mild effects on mood and subjective anxiety, while exerting effects consistent with GABA receptor modulation. Additionally, P is linked to motivation for affiliation / social contact; P (and ALLO) release may be especially responsive to social rejection. These observations lead to the novel hypothesis that stress-related P/ALLO production functions not only to down-regulate stress and anxiety, but also to promote social contact as a long-term coping strategy. Malfunctioning of the P/ALLO system could therefore underlie depression partly by decreasing propensity to affiliate with others.